Influence of Inflation on Poverty in Bima City - Junaidin Junaidin; Puji Muniarty (Ilomata International Journal of Management, 2020)
Inflation and poverty are important indicators in the economy, the pace and growth are always strived to be low and stable so as not to cause macroeconomic diseases which will later have an impact on instability on the economy. This study aims to analyze the effect of independent variables on the dependent variable. The independent variable in this study is inflation while the dependent variable is poverty in the City of Bima in the period 2013-2018. The sample in this study is in the form of inflation and poverty data for the past 6 years, namely from 2013 to 2018. The data used in this study are in the form of a list of tables regarding inflation and poverty for 6 years obtained from the Office of the Statistics Indonesia (BPS) office in Bima City. The data used are secondary data and the method used is simple linear regression analysis, simple correlation coefficient, simple linear determination and t-test (2 parties) using SPSS Version 20.0 to get a comprehensive picture of the relationship between one variable with another variable. The results showed that inflation had no effect and was not significant on poverty in Bima City.